Calculation of coaxial shunts superheat temperature; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Bedareva E. V. Elena Vyacheslavovna (2014, 2014)
Title screen